2011
DOI: 10.4103/1319-3767.80378
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of serum vascular endothelial growth factor and Interleukin-6 in patients with colorectal cancer

Abstract: Background/Aim:Some biological factors play a role in stimulation of malignant growth, metastasis and angiogenesis; however, their clinical relevance has not yet been well established for most of them. This work was aimed at studying the clinical relevance of serum vascular endothelial growth factor (VEGF) and interleukin -6 (IL-6), in patients with colorectal cancer (CRC).Materials and Methods:Preoperative serum levels of VEGF and IL-6 were measured by enzyme -linked immuno -assay in 35 CRC patients and in 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 23 publications
1
29
0
2
Order By: Relevance
“…IL-6, which acts as both a pro-inflammatory and anti-inflammatory cytokine, has a critical role in tumor development and progression. Patients with colorectal cancer had significantly higher vascular endothelial growth factor and IL-6 levels than healthy controls, 26 suggesting IL-6 is involved in tumor development. ET-1, which acts as an autocrine/paracrine factor, is expressed and involved in tumor growth and progression in many types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6, which acts as both a pro-inflammatory and anti-inflammatory cytokine, has a critical role in tumor development and progression. Patients with colorectal cancer had significantly higher vascular endothelial growth factor and IL-6 levels than healthy controls, 26 suggesting IL-6 is involved in tumor development. ET-1, which acts as an autocrine/paracrine factor, is expressed and involved in tumor growth and progression in many types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis is closely related to chronic inflammation (3), which is well known for its key roles in the development and progression of a variety of human cancers, including colorectal cancer (CRC) 2 (3,4). In the clinic, the serum levels of IL-6 and VEGF are significantly higher in CRC patients than healthy controls (5). Moreover, patients with advanced clinical stage disease have significantly higher levels of IL-6 and VEGF in the serum than those in early clinical stages (5).…”
mentioning
confidence: 99%
“…In the clinic, the serum levels of IL-6 and VEGF are significantly higher in CRC patients than healthy controls (5). Moreover, patients with advanced clinical stage disease have significantly higher levels of IL-6 and VEGF in the serum than those in early clinical stages (5). Although VEGF is one of the most potent endothelial cell mitogens (6 -9), IL-6, a critical inflammatory cytokine, may also be involved in angiogenesis in CRC (7,10,11).…”
mentioning
confidence: 99%
“…IL-6 is closely related to the invasion and metastasis of cancer, which might play pivotal but opposing roles in the host tumor interaction that, together with other immunoregulation components, determines the outcome for the development of local tumor immunity (33). High IL-6 levels have been detected in serum from colorectal cancer patients and shown the poor prognosis (34). Our study indicated that high levels of Th2 cytokines might have immunosuppression function in STCCB patients by suppressive effects on Th1 cytokines or inhibiting DCs function, or both together, which might result in tumor proliferation and recurrence.…”
Section: Discussionmentioning
confidence: 99%